Pengembangan Dakwah Pondok Pesantren Penghafal Alquran (PPPA) Raudhatul Jannah melalui Program Halal Tourism - Sidiq Pramana Widagda (Media Wisata, 2020)
The goal and target of tourism development in 2020 are increasing the image, competitiveness, and contribution of tourism in support of community welfare improvement as well as quality economic growth. This research uses the type of field research. The results of this study indicate that: PPPA Raudhatul Jannah made Halal Tourism program in improving the people's economy by providing services of tourism program by providing shelter and providing souvenirs in the form of learning Qur'an to be Tahfidz and Studying the Qur'anThe increase of tourist visit provides opportunities and challenges to the tourism to develop halal tourism. Training on the development of halal tourism make boarding school the heart of the economy by making the craft of sports tools in the form of bows and children are also some other equipment involving the surrounding community